2006
DOI: 10.1074/jbc.m607123200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Human von Willebrand Factor Studied Using Small Angle Neutron Scattering

Abstract: von Willebrand factor (VWF) binding to platelets under high fluid shear is an important step regulating atherothrombosis. We applied light and small angle neutron scattering to study the solution structure of human VWF multimers and protomer. Results suggest that these proteins resemble prolate ellipsoids with radius of gyration (R g ) of ϳ75 and ϳ30 nm for multimer and protomer, respectively. The ellipsoid dimensions/radii are 175 ؋ 28 nm for multimers and 70 ؋ 9.1 nm for protomers. Substructural repeat domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 49 publications
8
70
0
Order By: Relevance
“…Strong interactions of this protein with endogenous ProVWF seem unlikely because eotaxin-3 does not associate with VWF or Proregion under neutral conditions (pH 7.4) (Babich et al, 2009), similar to those that exist in the HUVEC ER (pH 7.2) (Erent et al, 2007). Large differences in apparent D of ProVWF-EGFP relative to ssEGFP alone (~50-fold) is unlikely to be due entirely to their different molecular masses (the predicted ratio of D assuming globular shapes is ~3), but rather to other factors such as the highly prolate molecular shape of soluble ProVWF (Singh et al, 2006) or interactions of ProVWF-EGFP with ER-resident components, possibly through its extensive sugar modifications. In common with the size dependences of mobilities in other cellular compartments (Dross et al, 2009;Lukacs et al, 2000;Papadopoulos et al, 2000;Seksek et al, 1997), the diffusion of soluble secretory proteins within the ER of HUVECs slowed sharply with increased protein size: the dependence of D on approximate molecular mass had a -1.6 logarithmic slope instead of the -0.33 slope predicted by the Stokes-Einstein formula (Fig.…”
Section: Soluble Wpb Cargo Is Freely Mobile In the Ermentioning
confidence: 78%
“…Strong interactions of this protein with endogenous ProVWF seem unlikely because eotaxin-3 does not associate with VWF or Proregion under neutral conditions (pH 7.4) (Babich et al, 2009), similar to those that exist in the HUVEC ER (pH 7.2) (Erent et al, 2007). Large differences in apparent D of ProVWF-EGFP relative to ssEGFP alone (~50-fold) is unlikely to be due entirely to their different molecular masses (the predicted ratio of D assuming globular shapes is ~3), but rather to other factors such as the highly prolate molecular shape of soluble ProVWF (Singh et al, 2006) or interactions of ProVWF-EGFP with ER-resident components, possibly through its extensive sugar modifications. In common with the size dependences of mobilities in other cellular compartments (Dross et al, 2009;Lukacs et al, 2000;Papadopoulos et al, 2000;Seksek et al, 1997), the diffusion of soluble secretory proteins within the ER of HUVECs slowed sharply with increased protein size: the dependence of D on approximate molecular mass had a -1.6 logarithmic slope instead of the -0.33 slope predicted by the Stokes-Einstein formula (Fig.…”
Section: Soluble Wpb Cargo Is Freely Mobile In the Ermentioning
confidence: 78%
“…For this purpose, we employed a water-soluble, non-cleavable, homobifunctional amine-reactive cross-linker BS3 with a history of successful use in stabilizing protein structures [10][11][12][13] . Figure 5 shows the chemical formula of BS3 and its cross-linking reaction with free epsilon amino groups of lysine in Strep-Tactin.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, that VWF could self associate and aggregate under high shear stress was known from previous studies. For instance, a shear-dependent self-association of VWF in suspension was demonstrated in a cone-plate viscometer [5]. These studies showed that in all cases the aggregation and web-formation process is essentially linked to the mechanical force generated by shear.…”
Section: Accepted M Manuscriptmentioning
confidence: 96%
“…At sites of high blood flow, von Willebrand factor (VWF) plays a central role in this process [1,2], as it primarily modulates platelet-subendothelium interaction by linking the platelet receptor GpIb/IX/V to the extracellular matrix [3,4]. In fact, when immobilized on subendothelial matrix, VWF forms a reactive surface capable of capturing platelets from flowing blood [5,6]. High shear stress causes micro-and macro-conformational changes of VWF from a globular state to a stretched chain [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation